Analysis of Students Biology Learning Difficulties in Senior High School - Herinda Mardin; Nurhayati Nurhayati B.; Ramlawati Ramlawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study is a survey study that aims to determine the biology topics that are difficult for students and teachers, the types of biology learning difficulties and how to overcome the biology learning difficulties of high school students in Palopo City. This research was conducted at all State Senior High Schools (SMA) in Palopo City. Data collection techniques using questionnaire techniques. Data were analysed quantitatively and qualitatively. The results of the study showed that the top 5 difficult biology topics for senior high school students in Palopo City were heredity, coordination system, circulatory system, genetic substance, mitosis and meiosis. While the biology topics that were difficult for students based on the perceptions of biology teachers of State Senior High Schools in Palopo City were metabolism. The types of biology learning difficulties experienced by students include various factors including student characteristics, teaching methods, and environmental limitations. From the various obstacles in learning biology experienced by students, solutions are needed to overcome them. Ways to overcome difficulties in learning biology according to students include suggested solutions involve improving teaching strategies, adjusting the curriculum, and increasing school support